Impedance characteristics analysis of rGO/polymers (PVDF, PMMA, PTFE) nanocomposite membranes. (2020) - Uniyal, Divya; Prasad, Brijesh; Nithin Kumar, K.C.; Chandra, Sarita; Panwar, Varij; Juneja, Pradeep; Agarwal, Vivechna; Gill, Fateh Singh
Abstract: In this work, the electrical impedance characteristic of different combinations of rGO/polymers (PVDF, PMMA, and PTFE) nanocomposites is presented. The nanocomposites membranes were prepared by solution casting method and characterized by SEM/EDX which revealed the distribution of rGO in membrane. The increasing loading of rGO reduced the real impedance values. The low wt% of rGO (i.e.0.5 wt%) showed capacitive behaviour with frequency whereas 1, 2, and 4 wt% (Higher concentration) of rGO membranes exhibited conductive behaviour (almost independent of frequency). The conduction in higher concentration nanocomposite membrane was due to interconnectivity of rGO sheets and tunnelling between close rGO sheets (<10 Å). Conduction in higher concentration membranes indicated percolation threshold. The Nyquist plots also indicated polarisation of membranes. The polarization at higher wt% might be due to capacitance of rGO. The applicability of conductive membranes can be explored for EMI shielding or as a biosensor due to its reactive property.